RASCH MODEL CLOZE TEST TO EVALUATE VOCABULARY OF ISLAMIC ELEMENTARY SCHOOL STUDENTS - Uswah, Maulidiyyatul; Ningrum, Ary Setya Budhi; Syafi'i, Muhammad Dliya Uddin (Premise: Journal of English Education and Applied Linguistics, 2025)
Numerous studies on cloze tests have been conducted regarding their beneficial use; however, research examining their efficacy for students in primary schools remains scarce. Consequently, existing cloze test designs often lack innovation and practicality for classroom implementation. A cloze test can be an alternative method for assessing elementary school students. Therefore, this study aims to develop a practical, innovative, and user-friendly cloze test tailored explicitly for elementary school students, providing teachers with a valuable tool to enhance vocabulary assessment. Hence, the Research and Development (R&D) under the ADDIE model is employed to develop the final product of English assessment, especially for fourth graders in elementary school. The average score percentage from linguistic and media experts was 93%, indicating that the test product was sufficiently good and ready for usage. The reliability was satisfactory, as indicated by a score of 0.73. The cloze test demonstrated an improvement in students' vocabulary mastery, as evidenced by the increase in scores from pre-test to post-test.